PAHs in seafood from the Mediterranean Sea: An exposure risk assessment. (May 2018) - Ferrante, Margherita; Zanghì, Guido; Cristaldi, Antonio; Copat, Chiara; Grasso, Alfina; Fiore, Maria; Signorelli, Santo Salvatore; Zuccarello, Pietro; Oliveri Conti, Gea
Abstract: Seafood represent an important food source for human, and seafood quality is associated with marine environment quality. PAHs are one of the main organic environmental contaminants and they can be introduced into the body through different way (ingestion, inhalation, dermal absorption). We present data on bioaccumulation of the sixteen PAHs, defined priority by the U.S.- EPA, in Sardina pilchardus, Solea solea and Donax trunculus, three species caught in the Catania Gulf and highly consumed by the local population. The risk to develop chronic systemic and carcinogenic effects due to the consumption of these target species was evaluated through the EDI, THQ and CR. EDI derived from D. trunculus ingestion falls within the range calculated by the EFSA. The THQ is less than 1, and the CR calculated for the Benzo(a)Pyrene is at the limit of the ARL (1✕10 −5 ). EDI derived from S. pilchardus and S. solea ingestion are below the range calculated by the EFSA. The THQ is less than 1, and the CR is below the acceptable risk level. The contamination level found in local seafood determines a low risk to develop chronic systemic effects, but the cancer risk could be of health concern especially for high-frequency molluscs consumers. Highlights: PAHs content was determined in D. trunculus, S. pilchardus and S. solea collected from the Catania Gulf. The risk to develop chronic systemic and carcinogenic effects due to the consumption of seafood was evaluated. Each PAHs shows a greater bioaccumulation profile in D. trunculus followed by S. pilchardus and finally S. solea. Local population is not particularly exposed to the chronic systemic effects derived from consumption of local seafood. Cancer risk could be of health concern especially for high-frequency molluscs consumers.